2014
DOI: 10.1016/s2095-3119(13)60670-x
|View full text |Cite
|
Sign up to set email alerts
|

Low Light Stress Down-Regulated Rubisco Gene Expression and Photosynthetic Capacity During Cucumber (Cucumis sativus L.) Leaf Development

Abstract: Low light stress down-regulated Rubisco gene expression and photosynthetic capacity during cucumber (Cucumis sativus L.) leaf development 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 43 publications
3
24
0
Order By: Relevance
“…Low temperature and weak light are the main environmental factors affecting tomato cultivation in Chinese solar greenhouse (Gao et al, 2010). Plants exposed to a combined low temperature and weak light stress have thinner and larger leaves compared with the leaves of plants grown under normal growth conditions (Murchie et al, 2005;Sun et al, 2014). The induced inhibition of growth caused by low temperature and weak light conditions may be involved in several physiological dysfunctions, including the reduction of photosynthetic efficiency, inhibition of biological carbon and nitrogen fixation, generation of reactive oxygen species (ROS), and membrane lipid peroxidation (H€ oglind et al, 2011;Sun et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Low temperature and weak light are the main environmental factors affecting tomato cultivation in Chinese solar greenhouse (Gao et al, 2010). Plants exposed to a combined low temperature and weak light stress have thinner and larger leaves compared with the leaves of plants grown under normal growth conditions (Murchie et al, 2005;Sun et al, 2014). The induced inhibition of growth caused by low temperature and weak light conditions may be involved in several physiological dysfunctions, including the reduction of photosynthetic efficiency, inhibition of biological carbon and nitrogen fixation, generation of reactive oxygen species (ROS), and membrane lipid peroxidation (H€ oglind et al, 2011;Sun et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Without the proper level of light and temperature that imposed on plant, growing proses will stunted [26,16]. Nevertheless, certain plants are able to assimilated with different environment to keep on survive [27,28]. Thus, there is need to conduct study to understand the effect of light intensity toward the effectiveness to reduce CO 2 by indoor plants.…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in RuBisCo activity is a hallmark of senescence (Secor et al, 1984 ; Ford and Shibles, 1988 ; Crafts-Brandner, 1992 ). Light affect expression of rbcL gene stimulates rbcL transcription and increases the transcription of rbcL (Kim et al, 2002 ; Sun et al, 2014 ). Low light had significant effect on RuBisCo; it down-regulated the gene expression of RuBisCo at transcript levels and resulted in the loss and inactivation of RuBisCo large subunit (Sui et al, 2011 ; Sun et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of SGR is closely associated with leaf senescence and fruit ripening (Barry et al, 2008 ; Yang et al, 2009b ). Researches have showed that light affects expression of ribulose-1,5-bisphosphate carboxylase/oxygenase ( rbcL ) gene, light stimulates rbcL transcription, and increases transcription of rbcL (Kim et al, 2002 ; Sun et al, 2014 ). RuBisCo content is associated with mRNA level of rbcL (Suzuki et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%